Incidence of managerial competencies in public innovation in the District Municipality of Amarilis, Huanuco - Caro Magni, Cesar A. (2024)
Objective: To determine the incidence of managerial competencies on public innovation in the District Municipality of Amarilis, Huánuco (Peru), by 2024. Materials and Methods: The study it is frame in a type of research of explanatory level, having been used a non-experimental design. Was selected a sample of 77 officials from the Amarilis District Municipality, to whom the survey technique was applied, and the questionnaire as an instrument. To analyze the data it is did use of the statistics descriptive, as well as inferential statistics to contrast the hypothesis. Results: A Spearman correlation coefficient of 0.509 was found, with a significance level of 0.001, which indicates that there is a positive, moderate, and significant relationship between managerial competencies, and public innovation in the Amarilis District Municipality, in 2024. This suggests that as the managerial competencies of municipal managers increase, he's also the level of innovation in the public sphere. Conclusions: It was evidenced that most officials and administrative workers mention that municipal managers have low levels of managerial competencies, and also that the Municipality has a low level of public innovation.